Exploring the predictors of zakat compliance in the community of farmers - Eka Setianingsih, Hesti; Irsyad, Mohamad; Velayati, Ajib Akbar (IAIN Surakarta, 2022)
Zakat plays an important role in reducing poverty. This study scrutinizes the influence of individual factors as proxied by attitude, subjective norm, and perceived behavioral control, demographic factors as proxied by Islamic educational background and gender, knowledge of zakat, and religiosity on farmers’ compliance in paying agricultural zakat in Ngawi Regency. Primary data were collected through questionnaires. The population in this study is farmers in Ngawi Regency Indonesia. 100 respondents were selected with a sampling technique carried out through purposive sampling. The result of Partial Least Squares Structural Equation Modeling (PLS-SEM) shows that attitude has no significant influence on zakat compliance. On the other hand, subjective norms, perceived behavioral control, Islamic educational background, knowledge of zakat, and religiosity have a positive influence on zakat compliance. This study indicates that gender is proven to have a negative influence on zakat compliance. This research contributes to providing valuable insight for zakat institutions to establish zakat collection policies based on individual perspectives.